Medical Reversals and Controversial Drug Therapies during COVID-19 Pandemic - Mansoor, Faraz; Kamran Saeed (Journal of Ayub Medical College Abbottabad, 2023)
Medical reversal can be defined as a phenomenon when statistically more powerful results of new clinical trials leads to a change of clinical practice. While the list of the treatments performed during this pandemic is a lengthy one and the pandemic is still ongoing, we will be mainly focusing on: Azithromycin, Anti-SARS-CoV-2 Monoclonal Antibodies, Chloroquine, Convalescent plasma, Hydroxychloroquine, Ivermectin, Remdesivir, Lopinavir and Ritonavir. One of the main reason of writing this manuscript is to highlight the challenges faced by the healthcare staff in finding a cure for this novel Corona Virus and the prevalemce of medical reversals in our clinical practice.